Sozialismus und Apokalyptik: Die politische Theologie des „kleinen" Otto Bauer - Giefing, Josef (2022)
,,Socialism and Apocalyptic" introduces political theology and the posthumous work of Otto Bauer (1897-1986). Bauer himself was from 1927 to 1934 chairman of the Federation of Religious Socialists (BRS) in Austria. His posthumous writings have been unpublished to date and represent an attempt at a political theology whose theological and philosophical interrelationships depict a specific interpretation of apocalyptic.